Gastrodin suppresses the amyloid β-induced increase of spontaneous discharge in the entorhinal cortex of rats - Chen, Peng-zhi (Neural plasticity, 2014)
Accumulated soluble amyloid beta- (Aβ-) induced aberrant neuronal network activity may directly contribute to cognitive deficits, which are the most outstanding characteristics of Alzheimer's disease (AD). The entorhinal cortex (EC) is one of the earliest affected brain regions in AD. Impairments of EC neurons are responsible for the cognitive deficits in AD. However, little effort has been made to investigate the effects of soluble Aβ on the discharge properties of EC neurons in vivo. The present study was designed to examine the effects of soluble Aβ(1-42) on the discharge properties of EC neurons, using in vivo extracellular single unit recordings. The protective effects of gastrodin (GAS) were also investigated against Aβ(1-42)-induced alterations in EC neuronal activities. The results showed that the spontaneous discharge of EC neurons was increased by local application of soluble Aβ(1-42) and that GAS can effectively reverse Aβ(1-42)-induced facilitation of spontaneous discharge in a concentration-dependent manner. Moreover, whole-cell patch clamp results indicated that the protective function of GAS on abnormal hyperexcitability may be partially mediated by its inhibitory action on Aβ(1-42)-elicited inward currents in EC neurons. Our study suggested that GAS may provide neuroprotective effects on Aβ(1-42)-induced hyperactivity in EC neurons of rats